Seismic hydrocarbon exploration : 2D and 3D techniques - Alsadi, Hamid N. (Springer, 2017)
This book presents the essential principles and applications of seismic oil-exploration techniques. It concisely covers all stages in exploration activities (data field acquisition, data processing and interpretation), supplementing the main text with a wealth of (>350) illustrations and figures. The book concentrates on the physics of the applied principles, avoiding intricate mathematical treatment and lengthy theoretical reasoning. A further prominent feature is the inclusion of a separate chapter on 3D surveying techniques and another, equally important chapter on seismic digital signals and the aliasing problem, which is presented in an accessible form. The book is designed to meet the needs of both the academic and industrial worlds. University students and employees of oil-exploration companies alike will find the book to be a valuable resource.- Resumé vydavatel
Keywords: seizmologie; ropa; zpracování dat; matematické modely; seismology; petroleum; data processing; mathematical models; elektronické knihy; monografie; electronic books; monographs